Predicting lymphoma development in patients with Sjögren's syndrome. (2nd September 2019) - De Vita, Salvatore; Gandolfo, Saviana
ABSTRACT: Introduction : The issue of predicting lymphoma in primary Sjögren's syndrome (pSS) starts from its clinical and biologic essence, i.e., an autoimmune exocrinopathy with sicca syndrome, inflammation and lymphoproliferation of MALT (mucosa-associated lymphoid tissue) in exocrine glands. Areas covered : The two major predictors to be firstly focused are persistent salivary gland (SG) swelling and cryoglobulinemic vasculitis with related features as purpura and low C4, or the sole serum cryoglobulinemia repeatedly detected. They are pathogenetically linked and reflect a heavier MALT involvement by histopathology, with the expansion of peculiar rheumatoid factor (RF)-positive clones/idiotypes. Other predictors include lymphadenopathy, splenomegaly, neutropenia, lymphopenia, serum beta2-microglobulin, monoclonal immunoglobulins, light chains, and RF. Composite indexes/scores may also predict lymphoma. Expert opinion : Prediction at baseline needs amelioration, and must be repeated in the follow-up. Careful clinical characterization, with harmonization and stratification of large cohorts, is a relevant preliminary step. Validated and new biomarkers are needed in biologic fluids and tissues. SG echography with automatic scoring could represent a future imaging biomarker, still lacking. Scoring MALT involvement in pSS, as an additional tool to evaluate disease activity and possibly to predict lymphoma, is welcomed. All these efforts are now ongoing within the HarmonicSS project and in other research initiatives in pSS.